Three-Year Study of Geriatric Skeletal Muscle Strength at a Top Referral General Hospital, West Java, Indonesi - Sigop Elliot Parsaulian Lumbantoruan; Vitriana Vitriana; Lazuardhi Dwipa (Althea Medical Journal, 2017)
Background: One of the aging effects is the decrease of skeletal muscle strength. The objectives of this study was to analyze the geriatric skeletal muscle strength by hand grip strength according to the characteristics of the elderly.Methods: An analytic retrospective study was carried out to 99 medical records of elderly who sought medication at the Geriatric policlinic of Dr. Hasan Sadikin General Hospital as the top referral hospital in West Java, Indonesia from 2012–2014. The result of hand grip strength measurement were grouped based on the characteristics of gender, age, body mass index (BMI), Barthel Index score, Mini Nutritional Assessment (MNA) score, number of disease and number of medication. All data were taken from patient’s medical records. The collected data were statistically analyzed with unpaired T-test and one way ANOVA test.Results: Among the 99 subjects, most of the subjects were male, under 80 years old,   independent living persons, had normal BMI, and normal nutritional level according to Mini Nutritional Assessment. Most of the subjects had more than 3 diseases per person and less than 5 sorts of medication. Male had higher hand grip strength compared to female and it was statistically significant (p=0.04). Based on ADL score, Independent living had higher hand grip strength compared to other level (p=0.008).Conclusions: From all the variables measured, only gender and  Activity Daily Living level contibute to the hand grip strength.